Implementasi Pemberian ASI pada Wanita Karir dalam Persepsi Hukum Islam - Habi, Muhamad Habibullah AR; Irani, Windy Adiska (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
This paper talks about giving breastfeeding from career women to children in terms of Islamic law. In this day and age, many women who choose to have a career are no exception for a woman who is married and is breastfeeding, usually a career woman whose house is close to the instant where she works is close, the woman (mother) will breastfeed her child during rest hours but if the institution where she works far from rukah, career women (mothers) will provide other alternatives such as formula milk or use a breast milk pump so that breast milk can be stored and used when the woman (mother) is not at home. The method used in writing this article is a qualitative research method and the source of the data that the author contains in this article is secondary data which contains theories related to research problems and primary data which is carried out by conducting direct interviews with respondents. Breastfeeding for career women who does not meet the maximum limit of breastfeeding, which is two years, but breastfeeding may not be full for two years, this is based on the al-Qur'an surah al-Baqarah verse 233 which reads "and mothers should breastfeed their children. for two years, for those who want to perfect "besides that it is also based on the Qaidah Fiqiyah which states that" fardhu is better than nafl " left out.